The effect OF DER, DPR, ROE, AND PBV ON stock return (Study on non-financial companies listed on the IDX in the period 2017-2019) - Lisiani Lisiani; Ratna Mappanyukki (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
The purpose of this study was to analyze the effect of DER, DPR, and ROE on stock returns with PBV as the intervening variable. The research population is non-financial companies listed on the Indonesia Stock Exchange. This study uses quantitative research with descriptive statistical methods to measure the level of influence of DER, DPR, ROE on stock returns through PBV in companies listed in Indonesia. The sampling method used is purposive sampling. The data used in this study is secondary data derived from financial statement information published through the Indonesia Stock Exchange website, namely in the 2017-2019 observation period. Analysis using multiple regression with path analysis. The results of the study conclude that DER, DPR, and ROE have no direct effect on PBV, DER and ROE have no direct effect on stock returns, while PBV and DPR have a direct effect on stock returns. PBV affects stock returns in a negative direction. DPR affects stock returns in a negative direction, which means that investors are more oriented towards investment projects that provide long-term returns. Sobel test results prove that PBV does not mediate the effect of DER, DPR, and ROE on stock returns. The novelty of this research is the PBV taken from the December financial statements as an intervening variable, while the stock return used is the realization of the average stock return two months after the announcement of the financial statements.